STUDI NUMERIK KARAKTERISTIK PENGABUTAN BAHAN BAKAR DIESEL, BIODIESEL DAN CAMPURANNYA - Hardiatama, Intan; Aziz, Muhammad Lutfi; Ilminafik, Nasrul; Sanata, Andi; Rosyadi, Ahmad Adib (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Biodiesel predicted to replace diesel fuel in the future that comes from the transesterification process of plant oils, animal fats, or used oils. One of the potential raw materials is nyamplung seeds because they are scattered in Indonesia, easy to cultivate, and bear fruit throughout the year [1]. The purpose of this study was to determine the effect of mixing pure diesel fuel and nyamplung biodiesel with the fuel composition B0, B20, B30, and B100 on the spray tip characteristics penetration, spray angle, and sauter mean diameter.This study focussed on simulation. The simulation method is carried out to predict the distribution and mean diameter of droplet using commercial fluent software. Fuel spray is carried out in free air with an injection pressure of 15 MPa, fuel temperature 28.2 ℃ and free air temperature 30.1 ℃. The spray process was taken at 6.25 ms and then the fuel spray characteristics were measured using the ImageJ application.The results of testing the fuel spray characteristics indicate that the amount of biodiesel content in the fuel is 20-100%. It can increase the length of spray tip penetration about 0.7-4.9%, a decrease in spray angle of 9.2-32.1% and the sauter mean diameter value increased by 20.1-84.6%. It caused by increasing the amount of biodiesel content in the fuel which results in an increase in the value of density, viscosity and surface tension of the fuel.